2007
DOI: 10.1017/s0007114507837469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of energy and casein or whey protein intake on bone status in a rat model of age-related bone loss

Abstract: In the elderly, nutritional deficiencies, such as low energy and protein intake, are suggested to increase the risk of osteoporotic fractures. Modulation of the amount and quality of protein intake under energy deficient conditions represents an interesting strategy to prevent aged-related bone loss. We investigated the effect of a 5-month dietary restriction on bone status in 16-month-old male rats. Rats were randomised into six groups (n 10 per group). Control animals were fed a normal diet containing either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 52 publications
3
12
1
6
Order By: Relevance
“…Indeed, in contrast with our previous findings in old rats (2,3), dietary restrictions did not induce body weight loss but only erased weight gain, suggesting a slowing down of the growth rate. The supplementation of dietary protein limited the bone loss due to energy deficiency, whereas it failed to improve bone status in old rats.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Indeed, in contrast with our previous findings in old rats (2,3), dietary restrictions did not induce body weight loss but only erased weight gain, suggesting a slowing down of the growth rate. The supplementation of dietary protein limited the bone loss due to energy deficiency, whereas it failed to improve bone status in old rats.…”
Section: Discussioncontrasting
confidence: 99%
“…At the diaphyseal site, femoral biomechanical properties were highly correlated with BMD values (r ϭ 0.618, p Ͻ 0.0001) and tended to be impaired by the two types of restriction. As previously reported, this observation might also be attributed to decreased diaphyseal cortical area, which contributes to bone fragility (3). Similarly, Talbott et al (18) observed decreased BMD and BMC, respectively, in rats after 9 and 16 wk of 40% energy restriction.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, because the protein intake was sufficient in all groups and within the normal range of intake (15-22%) [50, 51], we would expect no differential effect on bone. For example, a previous study found that even at 40% (vs. 17%) protein intake had no effect on bone parameters in older mice [52]. Similarly, the vitamin/mineral content differed slightly between groups since intake was lower in the HFD compared to the NFD group.…”
Section: Discussionmentioning
confidence: 97%
“…Energy restriction is known to decrease bone mass density in adult rats (37), indicating that the decreased energy balance in pmch Ϫ/Ϫ rats could result in osteoporosis. Hypogonadism is another known inducer of osteoporosis (15,63).…”
Section: E483mentioning
confidence: 99%